MicroRNAs and Long Non-coding RNAs in Genetic Diseases - Finotti, Alessia (Mol Diagn Ther, 2019)
Since the discovery and classification of non-coding RNAs, their roles have gained great attention. In this respect, microRNAs and long non-coding RNAs have been firmly demonstrated to be linked to regulation of gene expression and onset of human diseases, including rare genetic diseases; therefore they are suitable targets for therapeutic intervention. This issue, in the context of rare genetic diseases, is being considered by an increasing number of research groups and is of key interest to the health community. In the case of rare genetic diseases, the possibility of developing personalized therapy in precision medicine has attracted the attention of researchers and clinicians involved in developing “orphan medicinal products” and proposing these to the European Medicines Agency (EMA) and to the Food and Drug Administration (FDA) Office of Orphan Products Development (OOPD) in the United States. The major focuses of these activities are the evaluation and development of products (drugs, biologics, devices, or medical foods) considered to be promising for diagnosis and/or treatment of rare diseases or conditions, including rare genetic diseases. In an increasing number of rare genetic diseases, analysis of microRNAs and long non-coding RNAs has been proven a promising strategy. These diseases include, but are not limited to, Duchenne muscular dystrophy, cystic fibrosis, Rett syndrome, and β-thalassemia. In conclusion, a large number of approaches based on targeting microRNAs and long non-coding RNAs are expected in the field of molecular diagnosis and therapy, with a facilitated technological transfer in the case of rare genetic diseases, in virtue of the existing regulation concerning these diseases.